2013
DOI: 10.4103/0974-7796.115741
|View full text |Cite
|
Sign up to set email alerts
|

Endorectal coil MRI and MR-spectroscopic imaging in patients with elevated serum prostate specific antigen with negative trus transrectal ultrasound guided biopsy

Abstract: Background:The aim of this study was to see the efficacy of endorectal coil MRI and MR spectroscopic imaging in patients with elevated serum PSA and negative transrectal ultrasonography (TRUS)-guided biopsy.Materials and Methods:This study was conducted on 87 patients presented with: • Elevated prostatic specific antigen levels >5 ng/ml • Symptoms and signs of prostatic carcinoma • Patients with negative TRUS-guided biopsy • Suspicious lesion on TRU. All the patients were subjected to TRUS and followed by TRUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…One useful application of MRSI is in the detection of cancer in patients with rising PSA levels and prior negative biopsy. Ganie et al 73 performed MRSI in 87 patients with PSA >5 ng/ml and prior transrectal ultrasound (TRUS)-guided biopsy, and found that the addition of MRSI to conventional endorectal coil MRI improved detection of cancerous lesions, with a sensitivity of 87.3% and a specificity of 81.3%. A study by Kobus et al 74 examined the use of MRSI alone versus MRSI plus DW–MRI at 3T in 54 patients with biopsy-proven cancer before undergoing prostatectomy.…”
Section: Magnetic Resonance Spectroscopic Imagingmentioning
confidence: 99%
“…One useful application of MRSI is in the detection of cancer in patients with rising PSA levels and prior negative biopsy. Ganie et al 73 performed MRSI in 87 patients with PSA >5 ng/ml and prior transrectal ultrasound (TRUS)-guided biopsy, and found that the addition of MRSI to conventional endorectal coil MRI improved detection of cancerous lesions, with a sensitivity of 87.3% and a specificity of 81.3%. A study by Kobus et al 74 examined the use of MRSI alone versus MRSI plus DW–MRI at 3T in 54 patients with biopsy-proven cancer before undergoing prostatectomy.…”
Section: Magnetic Resonance Spectroscopic Imagingmentioning
confidence: 99%
“…The 1H-MRSI acquisition has evolved from singlevoxel spectroscopy to 3D 1H-MRSI that is typically acquired using phase encoding in all three directions but is time consuming. Improvements in pulse sequence design have enabled the acquisition of metabolic information from the entire prostate at high resolution within less than 10 min with voxel sizes ranging from 0.2 to 0.5 cm 3 , making 1H-MRSI a clinically feasible technique [139,140]. These include using flyback echo-planar readout gradients to improve efficiency and robustness to errors and non-uniform undersampling, and compressed sensing to accelerate the acquisition [141,142].…”
Section: Proton Magnetic Resonance Spectroscopic Imagingmentioning
confidence: 99%